Divergent Expression Patterns of miR164 and CUP-SHAPED COTYLEDON Genes in Palms and Other Monocots: Implication for the Evolution of Meristem Function in Angiosperms - Adam, Hélène; Marguerettaz, Mélanie; Qadri, Rashad; Adroher, Bernard; Richaud, Frédérique; Collin, Myriam; Thuillet, Anne-Céline; Vigouroux, Yves; Laufs, Patrick; Tregear, James W.; Jouannic, Stefan (Molecular biology and evolution, 2011)
In order to understand how the morphology of plant species has diversified over time, it is necessary to decipher how the underlying developmental programs have evolved. The regulatory network controlling shoot meristem activity is likely to have played an important role in morphological diversification and useful insights can be gained by comparing monocots and eudicots. These two distinct monophyletic groups of angiosperms diverged 130 Ma and are characterized by important differences in their morphology. Several studies of eudicot species have revealed a conserved role for NAM and CUC3 genes in meristem functioning and pattern formation through the definition of morphogenetic boundaries during development. In this study, we show that NAM- and CUC3-related genes are conserved in palms and grasses, their diversification having predated the radiation of monocots and eudicots. Moreover, the NAM-miR164 posttranscriptional regulatory module is also conserved in palm species. However, in contrast to the CUC3-related genes, which share a similar expression pattern between the two angiosperm groups, the expression domain of the NAM-miR164 module differs between monocot and eudicot species. In our studies of spatial expression patterns, we compared existing eudicot data with novel results from our work using two palm species (date palm and oil palm) and two members of the Poaceae (rice and millet). In addition to contrasting results obtained at the gene expression level, major differences were also observed between eudicot and monocot NAM-related genes in the occurrence of putative cis-regulatory elements in their promoter sequences. Overall, our results suggest that although NAM- and CUC3-related proteins are functionally equivalent between monocots and eudicots, evolutionary radiation has resulted in heterotopy through alterations in the expression domain of the NAM-miR164 regulatory module.